Rejection Sensitivity and Psychological Capital as the Mediators Between Attachment Styles on Social Networking Sites Addiction - Shan, Huanhuan; Ishak, Zahari; Li, Jingyi (Frontiers in Education, 2021)
This study was based on the framework of attachment, reinforcement sensitivity, and positive psychology theories. The main objective is to investigate rejection sensitivity and psychological capital as the mediators between attachment styles on social networking sites addiction. The sample comprised 607 college students, and the data was collected using an online survey owing to the rapid development and penetration of social networking sites in China. Results demonstrated a mediating effect between rejection sensitivity, psychological capital, and attachment styles on social networking sites addiction. Moreover, fearful style is predicted significantly and positively on social networking sites addiction. Preoccupied style and dismissive-avoidant style are not significant effect on social networking sites addiction after adding the mediating variables of rejection sensitivity and psychological capital. Furthermore, attachment styles also influence the social networking sites addiction due to their dual effect on rejection sensitivity and psychological capital. Overall, the findings suggest that weakening rejection sensitivity, and enhancing psychological capital can be considered in future studies as contributors to social networking sites addiction for prevention or intervention studies.